Environmental performance analysis: foundry industry case report - Rebelato, Marcelo Girotto [UNESP]; Saran, Luciana Maria [UNESP]; Cury, Vitor Bernardes [UNESP]; Rodrigues, Andreia Marize [UNESP] (Emerald Group Publishing Ltd, 2017)
Purpose - The purpose of this paper is to present a case report involving environmental performance analysis of a small Brazilian business from the foundry industry. Design/methodology/approach - An environmental performance indicator was developed (I-epa) which is calculated taking into consideration the weighting of potential environmental impacts of each residue/sub product generated, the relative spatial dispersion which each residue/sub product can reach, and the adequacy evaluation of final allocation accomplished by the company for each residue/sub product. Findings - Despite the evidence that the corporation do not conduct washing of gases emitted from the chimney of the foundry furnace, which consists an environmentally inadequate attitude, the result of I-epa = 97.50 percent was obtained. This favorable result is due to the adequate allocation given to residues generated in greater volume in the process, the molding sand. This sand is addressed to an industrial landfill, which is an environmentally adequate practice and approved by competent environmental authorities. Practical implications - The method used can be applied to measure the environmental impact generated by any business of the foundry sector industry. Originality/value - The originality of the work is in the developed method, which takes into account: the potential impact of each residue/sub product generated, the amount of each residue/sub product generated in a given time period, the dispersion that each residue/sub product can attain, and the evaluation of eventual allocation of each residue/sub product.
Keywords: Analytic hierarchy process (AHP); Environmental management; Environmental analysis index; Environmental indicators; Foundry